P15 Audit of outcome of ambulatory care emergency surgery patients. (22nd July 2022) - Walker, H; Freer, R; Angamuthu, N; Hart, C
Abstract: Introduction: A proportion of emergency surgical patients are discharged with outstanding tasks (clinical review, imaging to be requested or results followed-up) pending. The turnaround time of these tasks typically placed at the bottom of the emergency surgical on-call list is dependent on the on-call registrar or house officer. The aim was to analyse the outcomes of pending tasks on ambulatory care emergency surgical patients and explore means to improve. Methods: A retrospective audit of emergency surgical patients from October to December 2021 was performed using the daily on-call list database. Results: Among the 149 patients with pending tasks on an ambulatory care basis, 80 were excluded (duplicate entries, unclear tasks, non-valid reasons). 38% of patients remained on the list for more than 24 hours with pending tasks. Only 75% of patients had pending tasks completed. Patients waited for 3.3 hours on average (59 to 350 minutes) for clinical review by the registrar or house-officer. The reasons for the delay in clinical review and task completion narrowed down to inappropriate timing (scheduled return in the mornings, when the on-call team are either busy with the ward round or in theatres) and time restraints. Conclusion: Based on the above findings, it would be beneficial for our hospital to have a surgical hot clinic with staggered appointments rather than ad hoc return to the ambulatory unit. This would improve waiting times and would allow outstanding tasks to be completed by the surgical registrar or clinical fellow during clinic, increasing patient satisfaction. Take-home message: A dedicated surgical hot clinic will reduce patient waiting times, increase overall patient satisfaction and ensure completion of outstanding clinical tasks.